Thin Film Solar Cells: Fine‐Tuning the Sn Content in CZTSSe Thin Films to Achieve 10.8% Solar Cell Efficiency from Spray‐Deposited Water–Ethanol‐Based Colloidal Inks (Adv. Energy Mater. 24/2015). Issue 24 (December 2015) - Larramona, Gerardo; Levcenko, Sergiu; Bourdais, Stéphane; Jacob, Alain; Choné, Christophe; Delatouche, Bruno; Moisan, Camille; Just, Justus; Unold, Thomas; Dennler, Gilles
Abstract : In article number 1501404 Gerardo Larramona and co‐workers present the fabrication of thin film solar cells with a fast and low‐cost procedure using an aqueous Cu‐Zn‐Sn‐S colloidal ink deposited by nonpyrolitic spray, followed by annealing/selenization. By fine tuning the stoichiometry of the CZTSSe layer spray, an efficiency of 10.8% under simulated AM1.5G is reached. The upper part of the cover represents a cross section of the CZTSSe photoactive layer. The lower part is a top view of the complete devices.